ANALISIS AKUNTABILITAS, TRANSPARANSI DAN PENERAPAN ISAK 35 PADA PENGELOLAAN KEUANGAN MASJID JAMI ATH-THAYYIBAH - Auliah, Firdah; Manalu, Theresia Yosevani; Irwansyah, Dea Putri; Nabila, Anastacia (Jurnal Akuntansi Kompetif, 2025)
This study aims to analyze the application of accountability, transparency and ISAK 35 in the financial management of the Jami' Ath-Thayyibah Mosque. Mosques as non-profit entities have moral and social responsibilities in preparing accountable and transparent financial reports. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, direct observation, documentation, and field surveys. The results showed that the mosque management has implemented some of the principles of accountability, such as the preparation of the annual budget, reporting to the congregation and the foundation, and preparing the annual financial report. However, the internal monitoring system and performance evaluation have not been formally implemented. In the aspect of transparency, access to information to the congregation and involvement in budget planning have been carried out, but have not been supported by a legal framework and independent audits. In addition, the financial statements prepared are still limited to a recap of cash in and out, without reference to the reporting structure of ISAK 35 standard. The main obstacle lies in the limited human resources and the lack of technology utilization. The findings recommend increasing human resource capacity and digitizing reporting to strengthen accountability and transparency in religious institutions.